Strategic knowledge management : a conceptual framework - Miranda, Roberto Campos da Rocha (2005)
A conceptual model of Strategic Knowledge: Management (SKM) is presented as the main result of a research concluded in 2004, which aimed to develop a conceptual mode! of SKM. Thus, this paper, complete its model and establish the difference between Strategic Knowledge Management (SKM) and Knowledge Strategic Management (KSM). Using the inductive and deductive methods simultaneously, the methodology consisted of integrating general models of knowledge management with different strategic perspectives. Results seem to indicate a new topic of study in the organizational context, bringing together Business, Information Science and Psychology. In this regard, the model built up comprises three basic parts, namely: management features, kinds of knowledge and strategic issues. The research results point out the difference between SKM and KSM, based on its essence.